Analysis of The Influence of Transformational Leadership Style And Work Discipline on Employee Innovation Performance With Motivation As An Intervening Variable At SDIT Yogyakarta - Candra, Candra; Chandra Kirana, Kusuma; Hadi, Syamsul (RELASI : JURNAL EKONOMI, 2024)
This study aims to find out about the Analysis of the Effect of Transformational Leadership Style, Work Discipline, on Innovation Performance with Motivation as an intervening variable aimed at managing superior and advanced human resources in facing the era of globalization and quality human resources will develop high performance for the organization. One of them is by paying attention to the performance of employees both from their motivation and discipline in achieving the organization. This study uses a quantitative descriptive method with data analysis techniques Measurement Model (Outer Model): Convergent Validity, Discriminant Validity, Discriminant Validity, Reliability. Structural Model (Inner Model), Predictive Relevance (Q Square), Hypothesis Testing Results. Tested manually using the SmartPLS 3.2.9 software application. The population in this study were employee teachers at SDIT Luqman Al Hakim Yogyakarta, while for the sample data using the saturation technique, all employees were taken, namely 62 samples. The results showed that the coefficient value for the H1 coefficient was 0.288, the p-value was 0.007, the H2 coefficient was 0.343, the p-value was 0.003, the H3 coefficient was 0.339, the p-value was 0.000, the H4 coefficient was 0.327, the p-value was of 0.026, the H5 value, the coefficient value of 0.447 the p-value of 0.007 reveals that Transformational Leadership Style, and Work Discipline can improve employee innovation performance with Employee Work Motivation so that resources are able to develop high performance for the organization.